Effectiveness of computer-aided learning in oral health among patients and caregivers: A systematic review - Normaliza Ab Malik; Jiaguan Zhang; Otto Lok Tao Lam; Lijian Jin,; Colman McGrath (Oxford University Press, 2024)
Journal of the American Medical Informatics Association, 24(1), 2017, 209–217